2021
DOI: 10.1016/j.heliyon.2021.e07936
|View full text |Cite
|
Sign up to set email alerts
|

Detection of SARS-CoV-2 spike protein D614G mutation by qPCR-HRM analysis

Abstract: Objectives Monitoring the spread of the G614 in specific locations is critical as this variant is highly transmissible and can trigger the emergence of other mutations. Therefore, a rapid and accurate method that can reliably detect the D614G mutation will be beneficial. This study aims to analyze the potential use of the two-step Reverse Transcriptase quantitative polymerase chain reaction - high resolution melting analysis (RT-qPCR-HRM) to detect a specific mutation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…does not require complicated procedures for establishing or maintaining analytical performance as designing and validating increasing number of probes, or cumbersome technical replicatesOther sequence non-specific methods, such as High-Resolution Melting (HRM) may be valid alternatives. Nonetheless, HRM has been limited by inherently shorter amplicons and a longer running time (45)(46)(47)(48)(49)(50). Furthermore, HRM approaches are greatly limited to discrete mutations targeted to achieve consistency and reliability in performance (45)(46)(47)(48)(49)(50) In conclusion, the advantages for the healthcare systems of the flexible, cost-effective streamlined approach herein described, which integrates DHPLC with Sanger sequencing and, eventually, NGS should be considered as valuable alternative for variant screening in the genomic surveillance.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…does not require complicated procedures for establishing or maintaining analytical performance as designing and validating increasing number of probes, or cumbersome technical replicatesOther sequence non-specific methods, such as High-Resolution Melting (HRM) may be valid alternatives. Nonetheless, HRM has been limited by inherently shorter amplicons and a longer running time (45)(46)(47)(48)(49)(50). Furthermore, HRM approaches are greatly limited to discrete mutations targeted to achieve consistency and reliability in performance (45)(46)(47)(48)(49)(50) In conclusion, the advantages for the healthcare systems of the flexible, cost-effective streamlined approach herein described, which integrates DHPLC with Sanger sequencing and, eventually, NGS should be considered as valuable alternative for variant screening in the genomic surveillance.…”
Section: Discussionmentioning
confidence: 97%
“…Nonetheless, HRM has been limited by inherently shorter amplicons and a longer running time (45)(46)(47)(48)(49)(50). Furthermore, HRM approaches are greatly limited to discrete mutations targeted to achieve consistency and reliability in performance (45)(46)(47)(48)(49)(50) In conclusion, the advantages for the healthcare systems of the flexible, cost-effective streamlined approach herein described, which integrates DHPLC with Sanger sequencing and, eventually, NGS should be considered as valuable alternative for variant screening in the genomic surveillance.…”
Section: Discussionmentioning
confidence: 97%
“…Several PCR-based approaches have been developed for the rapid discrimination of SARS-CoV-2 variants in clinical samples, such as the RT-PCR melting temperature assay ( Banada et al, 2021a ; Banada et al, 2021b ) and multiplex qPCR target failure screening ( Vogels et al, 2021 ). The former method requires a clear difference in the annealing temperatures between the target mutation sequence and its opposite genotype, which could be affected by any additional mutations located in the target sequence ( Gazali et al, 2021 ). The multiplex qPCR target failure screening is based on deletions in the genome of SARS-CoV-2, and does not have good sensitivity and specificity since the rapid emergence of new mutations is the major concern.…”
Section: Introductionmentioning
confidence: 99%
“…Due to high sensitivity, HRM has been extensively used for single nucleotide polymorphism (SNP) detection. Besides, numerous studies have utilized HRM in diverse applications, e.g., detection of genetic diseases, mutations, bacteria, and genotyping. Recently, HRM has also been employed for SARS-CoV-2 variant identification and mutation detection . These studies have shown the feasibility of HRM as a practical genotyping tool for SARS-CoV-2 variant determination.…”
mentioning
confidence: 99%
“…23−29 Recently, HRM has also been employed for SARS-CoV-2 variant identification 30−32 and mutation detection. 33 These studies have shown the feasibility of HRM as a practical genotyping tool for SARS-CoV-2 variant determination. The use of HRM analysis to detect variants complements the existing detection method of SARS-CoV-2 by real-time reverse transcription PCR (qRT-PCR).…”
mentioning
confidence: 99%